Community Participation in Developing Penglipuran Village in Bali as Tourism Village - Rachmawati, Dewi; Fitriyani, Lamria Raya (Humaniora: Journal of Indonesia Culture and Society, 2024)
The research was conducted to determine the participation of the people of Penglipuran village in developing their village as a tourism village. Tourism development in an area certainly needed to be supported by the surrounding community. For this reason, community participation was essential, especially in tourism areas such as Penglipuran Tourism Village, Bali Island. The research applied a constructivism paradigm with descriptive qualitative research methods. The informants interviewed were the leaders of the traditional village, commonly called Kelian, as well as the people in Penglipuran village. The answers from the informants were analyzed using the theory of social change and the theory of community participation. Based on the results, community participation in Penglipuran village is on the partnership ladder. Currently, it is classified as a success because there is an opportunity for the community to be actively involved in conveying it to the village government. According to Cohen and Uphoff, in the decision-making process, Kelian, as a traditional village leader, has limited authority in connection with the concept of community participation. Program planning and decisions are formulated with all members of the village community. Likewise, during the implementation and evaluation stages of the program, even at the stage of enjoying the results, the entire village community is also involved.Â